It’s that time of the month!: development of digital intervention for adolescent menstrual health education - Saiful Bahri, Hannah Sabrina; Mohd Mohadis, Hazwani (KICT Publishing, 2025)
Adolescents worldwide face significant challenges in understanding and managing their menstrual health due to stigma, misinformation, and a lack of accessible, age- appropriate educational resources. Existing period tracking apps often fail to address the unique needs of younger users, offering limited educational content and complex interfaces that do not cater to their developmental stage. To bridge this gap, FemHealth is designed as a digital educational platform that provides adolescents with accurate cycle tracking, symptom management, and predictive algorithms for personalized insights. The platform integrates comprehensive, evidence-based educational content on menstrual health, hygiene, cycle irregularities, and emotional well-being, fostering menstrual literacy. Developed using the Agile methodology, FemHealth incorporates continuous feedback from adolescents and parents to ensure usability and relevance. By offering a confidential and supportive environment, FemHealth seeks to empower adolescents with the knowledge and confidence to navigate their menstrual health with greater autonomy and awareness.